Dimensional properties of wood cement panels produced from wood waste of some municipal tree species in University of Ibadan (2010)
A study was carried out to investigate the dimensional properties of cement bonded particle board from waste of 3 urban trees common in University of Ibadan campus. The 3 wood species used for board production are: Gmelina arborea, Delonix regia,and Samanea sena. The dimensional properties investigated are thickness swelling and water absorption. Data collected were subjected to analysis of variance (ANOVA) at 0.05 probability level. Results showed that the mean values obtained for the thickness swelling (TS) after 24- and 48-hours of water immersion ranged from 0.52% - 7.72% and 0.51% - 7.66%. Cement-bonded particleboard made from Gmelina arborea sawdust have the lowest value of thickness swelling of 0.51% followed by Samanea sena of 1.79% and least thickness swelling value of 5.96% from Delonix regia. The effect of wood species, mixing ratio levels and interaction were significantly different at 5% significance level. The mean value of obtained for the water absorption (WA) after 24- and 48-hours of water immersion ranged from 29.60%- 11.47% and 33.34% - 14.20%. All the wood species used in the production of cement-bonded particleboards show decrease in the physical properties assessed as the mixing ratio level of the cement binder increases in the production.